2017
DOI: 10.3390/molecules22122170
|View full text |Cite
|
Sign up to set email alerts
|

Natural Korean Medicine Dang-Gui: Biosynthesis, Effective Extraction and Formulations of Major Active Pyranocoumarins, Their Molecular Action Mechanism in Cancer, and Other Biological Activities

Abstract: Angelica gigas Nakai (AGN) is a crucial oriental medicinal herb that grows especially in Korea and the Far-East countries. It contains chemically active compounds like pyranocoumarins, polyacetylenes and essential oils, which might be useful for treatment of several chronic diseases. It has been used for centuries as a traditional medicine in Southeast Asia, but in Western countries is used as a functional food and a major ingredient of several herbal products. The genus Angelica is also known as ‘female ginse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 91 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…Many studies have shown that decursin and decursinol angelate are major compounds of Angelica gigas Nakai, and they are known to have primary responsibility for the anticancer effect of Angelica gigas Nakai [ 13 , 14 , 46 ]. Therefore, we also analyzed the composition of the AGN extract and found that decursin and decursinol angelate are major components of the AGN extract ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown that decursin and decursinol angelate are major compounds of Angelica gigas Nakai, and they are known to have primary responsibility for the anticancer effect of Angelica gigas Nakai [ 13 , 14 , 46 ]. Therefore, we also analyzed the composition of the AGN extract and found that decursin and decursinol angelate are major components of the AGN extract ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Angelica L. belonging to the Umbelliferae family is distributed in Asia, Europe, and North America and comprises more than 60 species [ 12 , 13 ]. In China, Japan, and Korea, Angelica L. has been used as a traditional herbal medicine for curing colds, pain, and anemia and has been known as the “female ginseng” due to its beneficial effects on female health [ 12 , 14 , 15 ]. Angelica L. contains a variety of bioactive metabolites, such as pyranocoumarins, essential oils, and polyacetylenes, which exhibit many beneficial effects, including anticancerous, anti-inflammatory, antifungal, antioxidant, and neuroprotective properties [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBLF exhibited antiproliferative and proapoptotic effects in the azoxy-methane/dextran sodium sulfate-induced in vivo model through decreasing the signal transduction pathway protein Akt in its activated form and increasing the activity of caspase-3 [ 19 ]. Finally, a review by Reddy et al described the chemical compounds of Angelica gigas Nakai and their biosynthesis, efficient extraction and formulation methods, and underlying mechanisms for chronic diseases such as cervical cancer, prostate cancer, melanoma, bladder and colon cancer, lung cancer, and sarcoma were summarized, providing useful information for researchers in this area [ 20 ].…”
mentioning
confidence: 99%